Clinical effect of delgocitinib 0.5% ointment on atopic dermatitis eczema intensity and skin barrier function. Issue 2 (1st October 2021) - Abe, Masatoshi; Iizuka, Hajime; Nemoto‐Hasebe, Ikue; Nemoto, Osamu; Toyama, Hiroyuki; Ohashi‐Doi, Katsuyo; Kabashima, Kenji
Abstract: Objectives: Delgocitinib is a small‐molecule JAK inhibitor that has recently been approved in Japan as the world's first topical JAK/STAT pathway inhibitor for the treatment of atopic dermatitis (AD). In this study, the effects of delgocitinib 0.5% ointment treatment on skin rash severity and skin‐barrier function were examined. Methods: Adult Japanese patients with mild‐moderate AD ( n = 23) were recruited into the trial. Healthy subjects ( n = 10) were examined in parallel. The effects of four weeks of treatment with delgocitinib 0.5% ointment on the partial eczema area and severity index (pEASI) score, stratum corneum hydration (SCH), and trans‐epidermal water‐loss (TEWL) were examined. Patient reported effects of the treatment were assessed by a questionnaire. Results: Four weeks of treatment showed a statistically significant improvement ( p < .001) in pEASI score of 61.8%, ±54.0 (mean%, SD) compared to baseline in AD patients. Improvement in SCH at four weeks (37.6AU, ±11.5 (mean, SD), p < .001) was achieved in AD patients compared to baseline (SCH = 24.9AU, ±8.8 (mean, SD)). A trend toward reduction in TEWL over time was seen in the active treatment group (TEWL = 9.1 g/h/m 2 at baseline, 7.1 g/h/m 2 at two weeks, and 6.9 g/h/m 2 at 4 weeks). The pEASI score and SCH and TEWL values improved from two‐to‐four weeks treatment. Patients reported perceived improvements after four weeks of treatment on all parameters associated with skin condition. No safety concerns were identified. Conclusions: Treatment with delgocitinib 0.5% ointment was well tolerated and showed improvements of both eczema and SCH in adult AD patients. Abstract : The study by Abe et al examines the effects of delgocitinib 0.5% ointment treatment on skin rash severity and skin‐barrier function in adult patients with mild‐moderate AD. Partial eczema area and severity index (pEASI) score, stratum corneum hydration (SCH) and trans‐epidermal water‐loss (TEWL) were examined. Four weeks of treatment showed a statistically significant improvement ( p < .001) in pEASI score of 61.8%, ±54.0 (mean%, SD) compared to baseline in AD patients. Improvement in SCH at four weeks (37.6AU, ±11.5 (mean, SD), p < .001) was achieved in AD patients compared to baseline (SCH = 24.9AU, ±8.8 (mean, SD)). Treatment with delgocitinib 0.5% ointment was well tolerated and showed improvements of both eczema and SCH in adult AD patients.